2014
DOI: 10.1021/jp405997r
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Band Gap in Metal–Organic Frameworks by Functionalizing Organic Linker: A Systematic Density Functional Theory Investigation

Abstract: A systematic investigation on electronic band structure of a series of isoreticular metal−organic frameworks (IRMOFs) using density functional theory has been carried out. Our results show that halogen atoms can be used as functional groups to tune not only the band gap but also the valence band maximum (VBM) in MOFs. Among halogen atoms (F, Cl, Br, I), iodine is the best candidate to reduce the band gap and increase the VBM value. In addition, it has been found that for the antiaromatic linker DHPDC (1,4-dihy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
74
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 46 publications
9
74
0
Order By: Relevance
“…As a first approximation, the band gap energy (Eg) can be estimated directly by extrapolating the longwavelength edge of the peak in the absorbance spectrum to zero. This result, although in agreement with recent reports, 5,16 is about 0.5 eV higher than the first measurements of MOF-5 band gap (∼ 3.4 eV) 9-12 which are still employed as reference for theoretical analysis and calculations of the optical properties of this material 36,37 . The result obtained for MOF-5 (usually considered as a direct semiconductor) indicates that Eg (MOF-5) = 3.86 eV ( Figure 6).…”
Section: Optical Propertiessupporting
confidence: 91%
See 1 more Smart Citation
“…As a first approximation, the band gap energy (Eg) can be estimated directly by extrapolating the longwavelength edge of the peak in the absorbance spectrum to zero. This result, although in agreement with recent reports, 5,16 is about 0.5 eV higher than the first measurements of MOF-5 band gap (∼ 3.4 eV) 9-12 which are still employed as reference for theoretical analysis and calculations of the optical properties of this material 36,37 . The result obtained for MOF-5 (usually considered as a direct semiconductor) indicates that Eg (MOF-5) = 3.86 eV ( Figure 6).…”
Section: Optical Propertiessupporting
confidence: 91%
“…More properly, it can be obtained by analyzing the dependence of the absorbance with the photon energy, according to the nature of the semiconductor (direct or indirect) 35 . However, even though calculations predict Eg values for MOF-5 near 3.4 eV, they favour the idea that the excitation is mainly localized in the ligand 36,38 . This result, although in agreement with recent reports, 5,16 is about 0.5 eV higher than the first measurements of MOF-5 band gap (∼ 3.4 eV) 9-12 which are still employed as reference for theoretical analysis and calculations of the optical properties of this material 36,37 .…”
Section: Optical Propertiesmentioning
confidence: 84%
“…The locations of the energy levels of the HOMO and LUMO determine the occurrence of the CO 2 photoreduction reaction. [94][95][96] Figure 4 summarizes the positions of the energy levels of the HOMO and the LUMO of typical semiconducting MOFs calculated by the aforementioned methods. [84] Recent research has shown that the HOMO-LUMO gap width of MOFs can also be obtained from UV-visible absorption spectroscopy by using the method of estimating the band gap width of inorganic semiconductors.…”
Section: Roles Of Mofs In Photocatalytic Co 2 Reductionmentioning
confidence: 99%
“…Furthermore, the functionalizations of organic linkers [94,95,97,98] and the modifications of the structures of metal clusters [99,100] in MOFs can both reduce their HOMO-LUMO gap width, leading to their expanded light-absorption capacity. Hence, most MOF photocatalysts can exhibit photocatalytic activities in a visible range, which is favorable to the improved light-utilization efficiency.…”
Section: Roles Of Mofs In Photocatalytic Co 2 Reductionmentioning
confidence: 99%
“…[75] More recently, the electronic band structures of a series of isoreticular IRMOFs was investigated, focussing in the impact of aromatic versus antiaromatic linkers or the impact of halogen atoms (F, Cl, Br, I) substituents on the parent benzene-dicarboxylic linker. [77] They provide a detailed interpretation of their results and possible guidelines for synthetic trials. One important conclusion of the work is that the tunability of the band gap depends again essentially on the chemical bonding of the organic linker, thus identifying iodine as the best candidate for a reduced energy gap and higher valence band maximum in the case of the bdc linker.…”
Section: Electronic Structures Of Mofsmentioning
confidence: 99%